First Report on Wild Occurrences of Phoenix Mushroom (Pleurotus pulmonarius Fr. Quél.) in Indonesia - Putra, Ivan Permana; Nurhayat, Oktan Dwi; Sibero, Mada Triandala; Hermawan, Rudy (Journal of Tropical Biodiversity and Biotechnology, 2024)
The genus Pleurotus is known as a commercially important mushroom and one of the most well-known cultivated mushrooms worldwide. Of many species of Pleurotus, the phoenix mushroom (P. pulmonarius) is cultivated in many countries, including Indonesia. In Indonesia, the farmers and larger companies usually use commercial strains of phoenix mushroom which they purchased from other countries. To date, there was no prior information regarding wild occurrences of P. pulmonarius in Indonesia. During our regular mushroom hunting in Sukabumi, West Java, Indonesia, some edible wild fruiting bodies of light brown Pleurotus were collected. The current study aimed to determine the taxonomical position of our specimens based on morphological and molecular evidence. The combination of morphological and molecular analysis confirmed our specimens as P. pulnonarius. Morphologically, our specimens were distinguished by the small to medium sized fruiting bodies, pileus light brown, pinkish brown, to pale brown, flabelliform in the beginning to expanding broadly ovoid in maturity, lamellae shortly to deeply decurrent, stipe fleshy, eccentric to lateral, concolorous with lamellae, Basidiospores cylindrical to ellipsoid, basidia clavate to club shaped, basidioles are abundant, oleiferous hyphae common. The BLAST result revealed that our specimens posed a high similarity to P. pulnonarius from several countries as the top hits. The ITS phylogenetic tree placed Pleurotus FIPIA-DEP51 in the same clade of P. pulnonarius with 100% BS value. This study reports for the first time the wild occurences of P. pulmonarius in Indonesia. Future study should be done to characterize the cultures of reported mushroom which can potentially be the local strain for cultivation of P. pulmonarius industry in Indonesia.